2022
DOI: 10.3389/fphar.2022.918689
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effects of oral Chinese patent medicines combined with western medicine in stable angina: A systematic review and network meta-analysis of 179 trials

Abstract: Background: Stable angina is a common condition with high morbidity and mortality rates. It has been reported that combining oral Chinese patent medicines (OCPMs) and Western medicine (WM) could potentially achieve a better effect than WM alone. However, the optimal OCPMs for stable angina remain controversial and merit further empirical research.Methods: PubMed, Embase, Web of Science, Cochrane Library, Ovid-Medline, Clinical Trials.gov, China National Knowledge Infrastructure, Wanfang Database, Weipu Journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…The effectiveness of TCM in the treatment of cardiovascular disease has been widely demonstrated in clinical practice (12)(13)(14)(15)(16). Despite high-quality randomized controlled trials being used in the current research, enhancing the external validity of clinical research and minimizing the differences between the trial and the real world are still necessary for translating research findings into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of TCM in the treatment of cardiovascular disease has been widely demonstrated in clinical practice (12)(13)(14)(15)(16). Despite high-quality randomized controlled trials being used in the current research, enhancing the external validity of clinical research and minimizing the differences between the trial and the real world are still necessary for translating research findings into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The findings were reported by a systematic review and meta-analysis of 19 eligible trials concluding that the combination of SBP with conventional treatment trial groups could significantly reduce the incidence of MACE, enhance left ventricular ejection fraction (LVEF), and lessen N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) levels [29]. Similarly, the results from a systematic review and network meta-analysis of 179 eligible trials suggested that SBP combined with Western medicine is presumably the optimal treatment prescription for both clinically effective and cardiovascular event rates [30]. The present evidence confirmed the relative long-term safety of SBP, which does not affect liver and kidney function or increase the risk of bleeding [14,23,28,31,32].…”
Section: Introductionmentioning
confidence: 99%